Galleria mellonella as a model host for human pathogens: recent studies and new perspectives - Junqueira, Juliana Campos [UNESP] (Taylor & Francis, 2012)
The number of studies using G. mellonella as a model host for human pathogens has increased significantly in the last few years. Important studies were published from different countries for evaluating the pathogenesis of bacterial and fungal infections and for exploring the host defenses against pathogens. Therefore, standardized conditions for the use of G. melonella larvae need to be established. Recent research showed that the deprivation of G. mellonella larvae of food during the experiment caused a reduction in immune responses and an increased susceptibility to infection, suggesting that incubating of larvae in the presence or absence of nutrition may affect the results and comparisons among different laboratories.
Keywords: Insect protein; Animal; Candida albicans; Candidiasis; Immunology; Larva; Metabolism; Moth; Note; Animals; Candidiasis; Insect Proteins; Larva; Moths